Explanation of the Decorations and Ornamentation's Used in Qajar Houses of Tabriz for Application in Contemporary Residential Design Education (Case Study: Mashroota, Hariri, and Ali Missieu Houses) - Sahar Shafiee; Mehrvash Kazemi Shishvan (اکولوژی انسانی, 2025)
This study examines the decorations and architectural ornaments of Qajar houses in Tabriz in order to extract concepts and patterns for use in the design of contemporary residential homes. The primary objective of this research is to analyze and identify the decorations used in Qajar houses of Tabriz and their applicability in the education of contemporary residential design. The research method is qualitative, based on content analysis. Open coding was used to analyze the data, through which key concepts and categories were identified. Data were collected through semi-structured interviews with 20 experts, and three Qajar houses in Tabriz (the Mashroota, Hariri, and Ali Missieu houses) were selected as case studies. The analysis was performed using Maxqda software. The findings of this study indicate that the decorations and ornamentations used in these houses, such as stucco work, mirror work, tile work, and wood carving, have a significant impact on shaping architectural identity and strengthening the sense of place. These decorations, in addition to their aesthetic value, influence the functionality of spaces and create a spiritual connection with the environment. They can also be utilized in the design of contemporary houses. Ultimately, the results show that the decorations and ornamentations of Qajar houses in Tabriz are important not only from an aesthetic standpoint but also in terms of functionality in space design, and they can serve as models for designing contemporary homes in a way that preserves historical and cultural identity.